KUALITAS PELAYANAN, PERSEPSI HARGA, DAN CITRA DESTINASI SEBAGAI FAKTOR PENENTU KEPUTUSAN KUNJUNGAN DI KRISNA WATERSPORT TEMUKUS, BALI UTARA - Putra, I Putu Wahyu Santana; Yudiaatmaja, Fridayana; Suci, Ni Made (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
This study examines the effect of service quality, price perception, and destination image on tourists’ visiting decisions at Krisna Watersport Temukus. This research is motivated by the increasing competition among water-based tourism destinations in North Bali and the challenges faced by Krisna Watersport in maintaining visitor numbers, especially among domestic tourists. A quantitative approach with a causal research design was used. Primary data were collected through questionnaires distributed to 160 respondents who had previously visited Krisna Watersport Temukus using a purposive sampling technique. The data were analyzed using multiple linear regression, supported by classical assumption tests, F-tests, and t-tests. The results show that service quality, price perception, and destination image each have a positive and significant effect on tourists’ visiting decisions. In addition, these three variables simultaneously have a significant influence on visiting decisions. These findings indicate that improving service quality, offering competitive prices, and strengthening destination image are important strategies to increase tourists’ visiting decisions at Krisna Watersport Temukus